The Impact of Neoliberalism on Models of Science Communication - M. D. Krynzhina (Концепт: философия, религия, культура, 2022)
National science is being transformed under the influence of global processes, which are mainly, although not entirely, dictated by the dominance of neoliberal ideas in a wide range of developed and developing countries. The term neoliberalism, (or neo-liberalism), which was coined in the 20th century, offers recommendations that include a set of political, economic, and ideological actions. The article examines the impact of the neoliberal turn in science on the process of interaction between science and society. It is substantiated that this affects the development of vector models for the spread of scientific neoliberal ideology. Academia is a research field that deals with a wide range of issues from actual dissemination of scientific research to the models of involving new constituencies, in which non-professionals are encouraged to participate in research via scientific discussions and polls. Academia is a global and debatable topic to be discussed. It should be noted that scientific communications as a process of promoting scientific knowledge outside the scientific communities have not been thoroughly studied by domestic researchers yet. In the international scientific community and the Russian scientific field, until recently, the understanding of the tasks of scientific communication varied greatly. However, the development of scientific communities is widespread in different countries and reveals the impacts of neoliberalism research on this process. The neoliberal initiative encourages the creation of conditions in which, firstly, citizens take an active part in solving scientific issues. And secondly, the prestige of the pursuit of pure science does not deter researchers from promoting commercialization and the free development of their scientific activity. The peculiarities of interaction between science and society are regarded from the point of view of the Italian sociologist Massimiano Bucchi. Distinguished in academic discourse for his classification of relationships among science, technology, and society, M. Bucchi specifies three patterns for such relationships: deficit, dialogue, and completion.